Accumulation of population polymorphisms in the mitonuclear genome with probable adaptive effect to extreme environments as altitude for forensic purposes - Iannacone, G. C. (2022)
We analyzed the accumulation of population polymorphism in 2504 individuals - nuclear genomes (nDNA) of 26 populations (81 genes associated to extreme environments) and 3295 mitochondrial genomes (mtDNA) of 47 populations with the aim to found mitonuclear relationship associated an extremes environment as altitude. For that, we use an algorithm developed by us to determine the accumulation of polymorphisms by segments in the genome and thus be able to perform the multivariate analysis to found SNPs differences and similarities among populations. The results showed in Peruvian population a statistically significant mitonuclear relationship for 113/293970 nDNA SNPs in 16/81 genes. In the case of the mtDNA, we found a statistically significant mitonuclear relationship for 6/22 mtDNA positions – Gene. Additionally for the Peruvian population, the MRPP3 had the greatest polymorphism contribution with respect to other populations. Then, these nDNA and mtDNA SNPs in genetically close populations to Peru can be applied to forensic genomic phenotyping to identify groups likely adapted to extreme conditions (such as altitude) or make individualization between low and high altitude populations.